PENGARUH KOMUNITAS DAN KEPADATAN RAYAP TANAH TERHADAP KERUSAKAN RUMAH - Ginuk Sumarni; Agus Ismanto (Pusat Penelitian dan Pengembangan Hasil Hutan, 1989)
The study was carried out at Cibadak, Padalarang and Pacet which have soil types of Renzina, litosol and brown forest soil complex; Brown mediteran complex and Brown Andosol and brown regosol association, respectively. It is found that the first soil type has the highest subterranean termites density as well as house damages.Subterranean termites species found at the whole locations are Macrotermes gilvus (Hagen) and Microtermes insperatus Kemner.